Pembuatan dan Karakterisasi Katalis Bifungsional dari Zeolit Alam - Suharto, Totok Eka; Gustian, Irfan; Sudaryono, Agus (GRADIEN : Jurnal Ilmiah MIPA, 2007)
Bifunctional zeolite catalysts have been prepared by three following steps: activation of local natural zeoliteby hydrochloric acid and ammonium nitrate solutions, followed by impregnation of Cr, Ni, and Ti ions separately, and finally by calcination at 500oC for 4 hours. Characterization of catalyst properties was conducted by XRD to analyze its crystal phases, by SEM to study its surface morphology, by methylene blue to determine its surface area, and by IR spectroscopic and adsorbed ammonia gravimetric methods to analyze acidic properties. X-ray difractograms show that all calcined catalysts have amorphous and dominant crystalline phases. The morphology of catalysts analyzed by SEM prohibited similar cracked lamellar layers on the surface characterized by a microporous material. These catalysts have high specific surface area of 110 m2/g. Acid amount measured by adsorbed ammonia gravimetric method is in a range of 3.00 – 3.70 mg NH3/g.